2014
DOI: 10.5090/kjtcs.2014.47.4.434
|View full text |Cite
|
Sign up to set email alerts
|

A Treatment Case of Endoscopic Removal of Left Ventricular Thrombus, During Coronary Artery Bypass Graft

Abstract: Left ventricular thrombus is a common complication related to acute myocardial infarction. Removing this with an incision of the free wall of the left ventricle may cause fatal cardiac dysfunction or arrhythmias. Furthermore, performing incision and suture on the fragile myocardium of an acute myocardial infarction patient may cause serious bleeding complications. If there is a patient with left ventricular thrombus who needs thoracotomy for another reason, the case is attempted with the thought that if effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In 12 studies, the follow-up was longer than 30-days and no mortalities were observed [2, 3, 5, 6, 8, 9, 12, 25, 26, 31, 33, 35]. The only postoperative complication observed was one case of atrial fibrillation (2.2%, 1/46).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 12 studies, the follow-up was longer than 30-days and no mortalities were observed [2, 3, 5, 6, 8, 9, 12, 25, 26, 31, 33, 35]. The only postoperative complication observed was one case of atrial fibrillation (2.2%, 1/46).…”
Section: Resultsmentioning
confidence: 99%
“…In 13 studies, the type of endoscope used was not specified [ 4 , 6 , 10 , 15 , 20 , 24 – 28 , 31 , 34 , 35 ]. Other adjunct endoscopic instruments such as forceps, graspers, scissors, suckers or retractors were used in 13 studies [ 2 , 3 , 12 , 13 , 15 , 19 , 21 , 25 , 30 , 32 , 34 , 35 , 37 ]. In the remaining it was not clear whether open surgical or endoscopic instruments were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the scarcity of available data, surgical removal of LVT was not proposed because the risk of embolism caused by LVT may not outweigh the surgical risks. 4 Nearly all the studies of surgically removing LVT were case reports 5 , 6 and lacked high‐quality research or evidence to instruct clinical practice of managing LVT patients who underwent left ventricular thrombectomy.…”
Section: Introductionmentioning
confidence: 99%